Network and systems medicine (Mary Ann Liebert, Inc, 2020)
"The premier open access, peer-reviewed journal focused on interdisciplinary approaches to exploiting the power of big data by applying systems biology and network medicine."
Keywords: Medicine : Periodicals; System analysis : Medicine : Periodicals; Systems biology : Periodicals; Big data : Periodicals; Systems Biology; Big Data; Big data; Medicine; Systems biology